Writing Cumbia Villera: Intermediality, Performance, and Neoliberalism in Washington Cucurto and Gabriela Cabezón Cámara - Hankin, Charlie D. (Revista Canadiense de Estudios Hispánicos, 2022)
Following the 2001 crisis in Argentina, cumbia villera emerged as a national music. Writers such as Washington Cucurto and Gabriela Cabezón Cámara incorporated the genre in their novels to reevaluate the political function of art in a neoliberal context. This article has two objectives: to consider the intermediality between cumbia and literature in two post-crisis novels; and to analyze how this intermediality engages with and reconfigures notions of neoliberalism. I propose to read cumbia-literature as an expression of what Verónica Gago calls a “neoliberalism from below,” which, in its most utopian iterations, wields the possibility of renewing democratic dissensus.